bài 1 tìm x
a) 3/x-5 bằng -4/x+2
b) x+3/-4 bằng -9/x+3
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1)
a)\(\dfrac{20}{30}+\dfrac{9}{30}=\dfrac{29}{30}\)
b)\(\dfrac{16}{24}-\dfrac{15}{24}=\dfrac{1}{24}\)
c)\(\dfrac{12}{63}=\dfrac{4}{21}\)
d) \(\dfrac{5}{6}x\dfrac{3}{4}=\dfrac{15}{24}=\dfrac{5}{8}\)
2)
a)\(x=\dfrac{5}{4}-\dfrac{2}{3}\)
\(x=\dfrac{7}{12}\)
b) \(x=4x\dfrac{3}{5}\)
\(x=\dfrac{12}{5}\)
\(\frac{-x}{4}=\frac{-9}{x}\)
\(\Rightarrow-x\cdot x=-9\cdot4\)
\(\Rightarrow-x^2=-36\)
\(\Rightarrow-x^2=-6^2\)
\(\Rightarrow-x=-6\)
\(\Rightarrow\) \(x=6\)
\(\frac{x-1}{9}=\frac{8}{3}\)
\(\Rightarrow\left(x-1\right)\cdot3=9\cdot8\)
\(\Rightarrow\) \(3x-3=72\)
\(\Rightarrow\) \(3x=72+3\)
\(\Rightarrow\) \(3x=75\)
\(\Rightarrow\) \(x=75\div3\)
\(\Rightarrow\) \(x=25\)
a,Cách 1: (6/11 + 5/11 ) x 3/7 Cách 2 :(6/11 + 5/11) x 3/7
= 1 x 3/7 =6/11 x 3/7 + 5/11 x 3/7
= 3/7 = 18/77 + 15/77
= 3/7
b, Cách 1:3/5 x 7/9 - 3/5 x 2/9 Cách 2 :3/5 x 7/9 - 3/5 x 2/9
= 7/15 - 2/15 = 3/5 x (7/9 - 2/9 )
= 1/3 = 3/5 x 5/9
= 1/3
c, Cách 1:(6/7 - 4/7) : 2/5 Cách 2: ( 6/7- 4/7 ) : 2/5
= 2/7 : 2/5 = 6/7 : 2/5 - 4/7 : 2/5
= 5/7 = 15/7 - 10/7
= 5/7
d,Cách 1:8/15 : 2/11 + 7/15 : 2/11 Cách 2:8/15 : 2/11 +7/15 : 2/11
= 88/30 + 77/30 =(8/15+7/15) :2/11
= 11/2 = 1 : 2/11
= 11/2
Bài 2 cậu tự làm nhé !
b: \(\dfrac{5}{7}-\dfrac{2}{3}\cdot x=\dfrac{4}{5}\)
=>\(\dfrac{2}{3}x=\dfrac{5}{7}-\dfrac{4}{5}=\dfrac{25-28}{35}=\dfrac{-3}{35}\)
=>\(x=-\dfrac{3}{35}:\dfrac{2}{3}=\dfrac{-3}{35}\cdot\dfrac{3}{2}=-\dfrac{9}{70}\)
c: \(\dfrac{1}{2}x+\dfrac{3}{5}x=-\dfrac{2}{3}\)
=>\(x\left(\dfrac{1}{2}+\dfrac{3}{5}\right)=-\dfrac{2}{3}\)
=>\(x\cdot\dfrac{5+6}{10}=\dfrac{-2}{3}\)
=>\(x\cdot\dfrac{11}{10}=-\dfrac{2}{3}\)
=>\(x=-\dfrac{2}{3}:\dfrac{11}{10}=-\dfrac{2}{3}\cdot\dfrac{10}{11}=\dfrac{-20}{33}\)
d: \(\dfrac{4}{7}\cdot x-x=-\dfrac{9}{14}\)
=>\(\dfrac{-3}{7}\cdot x=\dfrac{-9}{14}\)
=>\(\dfrac{3}{7}\cdot x=\dfrac{9}{14}\)
=>\(x=\dfrac{9}{14}:\dfrac{3}{7}=\dfrac{9}{14}\cdot\dfrac{7}{3}=\dfrac{3}{2}\)
Bài 2:
a: \(A=\left(x+1\right)^3+5=20^3+5=8005\)
b: \(B=\left(x-1\right)^3+1=10^3+1=1001\)
Bài 1:
a) \(x.\dfrac{3}{4}=\dfrac{9}{14}\)
\(\Rightarrow x=\dfrac{9}{14}:\dfrac{3}{4}\)
\(\Rightarrow x=\dfrac{6}{7}\)
b) \(x:\dfrac{5}{9}=\dfrac{3}{10}\)
\(\Rightarrow x=\dfrac{3}{10}.\dfrac{5}{9}\)
\(\Rightarrow x=\dfrac{1}{6}\)